Stuart's cape - Pennypacker, Sara, 1951- (Orchard Books, 2002)
Bored because there is nothing to do in the house to which his family has just moved and worried about starting third grade in a new school, Stuart makes a magical cape out of his uncle's ties and has a series of adventures.